Options and volatility effects in South Africa - Wandmacher, Ralf (Division of Actuarial Science, 2016)
This thesis examines and extends research into option price modeling in the South African market with a particular focus on its most important parameter, namely the volatility of the underlying. The primary objective of the thesis therefore is to offer an option price model that takes account of the conditions of the environment prevailing in South Africa. The initial aim of the thesis is to describe the behaviour of the volatility in the South African market. This is achieved by conducting three empirical examinations using data from the South African Futures Exchange (SAFEX). The empirical examinations are partly based on standard methodologies (that have been modified in the thesis) and partly based on original methodologies adapted for the South African environment.